Experimental investigation of the effect of high strain rate loading on the flexural behaviour of the steel fibre-reinforced concrete - Bakhshi, Mohammad (2021)
Steel-fibre-reinforced concrete (SFRC) with hooked end steel fibres was specifically designed for the fabrication of urban furniture, which are capable of providing protection against impact and blast loads. Considering the type of actions that are imposed on these structural elements, it was considered important to evaluate the effect of high strain rates on the flexural behaviour of SFRC material. In this research, three-point bending tests were conducted and the loading was applied considering various strain rates. Quasi-static tests were carried out with loads imposed by a servo-hydraulic machine at four different strain rates that ranged between 10-6 and 10-2 s-1. In addition, impact tests were performed, using a drop-weight impact test machine and considering three different drop heights that correspond to strain rates ranging from 1 to 20 s-1. The instrumentation adopted for this experimental program includes two fast response load cells, a high-speed response data acquisition, two high-capacity accelerometers, and a strain gauge. The load cells measured the total impact force and one reaction force, whose information was used to evaluate the inertia force. Additionally, two accelerometers measured the maximum acceleration at the beams’ midspan. Quasi-static and dynamic load-deflection relations, dynamic flexural tensile strength, and failure mode of SFRC were analysed and discussed.